Five-factor model personality traits in sport climbers - Marczak, Milena; Ginszt, Michał (Journal of Education, Health and Sport, 2017)
Background: Success in sport climbing depends both on physiological and psychological factors. Personality, a psychological factor influencing daily functioning, is connected with sport activities such as the choice of discipline and the approach to workout. Personality also affects athletic performance, emotional balance during sport activity and gaining new sports experiences. Aim: The aim of this study is to compare the personality traits in male and female sport climbers. Material and methods: We examined 60 sport climbers (30 men, 30 women) aged 23±1 years. The average time of climbing training was 6 years. The study used the Big Five Personality Inventory (NEO-FFI) in Polish adaptation. The questionnaire consists of 60 assertive statements, the truthfulness of which is assessed by the investigator on the five-point scale Neuroticism, Openness to experience, Conscientiousness, Agreeableness, and Extraversion. Results: The results showed there were significant differences between the two groups on the Openes to experience and Agreeableness scales. There were no significant differences in Neuroticism, Conscientiousness and Extraversion scales. Conclusions: Male sport climbers were more liberal in views and experience, whereas female sport climbers were more competing. Sport climbers of both sexes had high levels of emotional balance and extroversion, and the average level of conscientiousness.